2011
DOI: 10.2215/cjn.02400311
|View full text |Cite
|
Sign up to set email alerts
|

Warfarin in Atrial Fibrillation Patients with Moderate Chronic Kidney Disease

Abstract: SummaryBackground and objectives The efficacy of adjusted-dose warfarin for prevention of stroke in atrial fibrillation patients with stage 3 chronic kidney disease (CKD) is unknown.Design, setting, participants, & measurements Patients with stage 3 CKD participating in the Stroke Prevention in Atrial Fibrillation 3 trials were assessed to determine the effect of warfarin anticoagulation on stroke and major hemorrhage, and whether CKD status independently contributed to stroke risk. High-risk participants (n ϭ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
84
0
6

Year Published

2014
2014
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 184 publications
(93 citation statements)
references
References 25 publications
3
84
0
6
Order By: Relevance
“…Rivaroxaban was non-inferior to warfarin for the prevention of stroke and systemic embolism in the intent-to-treat 412 This finding is supported by a large Swedish database, in which stroke risk was lower in CKD patients with AF treated with warfarin (adjusted HR 0.76; 95% CI 0.72-0.80), 413 while bleeding was also slightly increased, especially during therapy initiation. 414 In a meta-analysis of the major NOAC trials, patients with mild or moderate CKD suffered fewer strokes, systemic emboli, or major bleeding events on NOACs than on warfarin.…”
Section: Rivaroxabanmentioning
confidence: 65%
“…Rivaroxaban was non-inferior to warfarin for the prevention of stroke and systemic embolism in the intent-to-treat 412 This finding is supported by a large Swedish database, in which stroke risk was lower in CKD patients with AF treated with warfarin (adjusted HR 0.76; 95% CI 0.72-0.80), 413 while bleeding was also slightly increased, especially during therapy initiation. 414 In a meta-analysis of the major NOAC trials, patients with mild or moderate CKD suffered fewer strokes, systemic emboli, or major bleeding events on NOACs than on warfarin.…”
Section: Rivaroxabanmentioning
confidence: 65%
“…2,5,10,12,13,15,17,18,20,21 Different equations were used for estimating the eGFR and classifying patients as having CKD: Cockcroft-Gault formula was used in 5 studies 15,18,20,21,25 collaboration and cystatin C clearance were also used for assessing the safety and efficacy of apixaban and dabigatran at different levels of eGFR. The remaining selected studies for the systematic review did not use any of these, because the diagnosis of CKD was retrieved from codification.…”
Section: Resultsmentioning
confidence: 99%
“…Information concerning the risk of stroke or systemic embolism in patients with AF who were also on dialysis was provided by only 1 study: in the national Danish registry thromboembolism was found to be increased in this specific population (HR 1.83, 95% CI 1.56 to 2.14, p <0.00001). 5 Baseline data, design, and the main findings of trials providing information regarding warfarin in this setting 5,15,17,18,20,21,23,25 are listed in Table 1. Information concerning time in therapeutic range is only known for the 3 included randomized controlled trials of the novel oral 18 and 62% in Apixaban for Reduction In STroke and Other ThromboemboLic Events in atrial fibrillation [ARISTOTLE] 21 trials).…”
Section: Resultsmentioning
confidence: 99%
“…Leczenie przeciwzakrzepowe można bezpiecznie stosować u pacjentów z umiarkowaną i umiarkowanie ciężką CKD ([współczynnik przesączania kłębuszkowego (GFR) ≥ 15 ml/min]: CKD w 3. stadium (oszacowany GFR < 59 ml/min/1,73 m 2 ) występowała u 805 spośród 1936 pacjentów objętych randomizacją w badaniu Stroke Prevention in Atrial Fibrillation (SPAF) i w tej grupie uzyskano dobre efekty leczenia warfaryną (INR 2-3) [412]. Te wyniki potwierdzono w dużej szwedzkiej bazie danych, w której stwierdzono, że ryzyko udaru mózgu było mniejsze u pacjentów z AF i CKD leczonych warfaryną (skorygowany HR 0,76; 95% CI 0,72-0,80) [413], natomiast ryzyko krwawienia było nieco zwiększone, zwłaszcza podczas rozpoczynania leczenia [414].…”
Section: Doustne Leczenie Przeciwzakrzepowe U Pacjentów Z Migotaniem unclassified